Image and city: The shrinking of the look - Capelato, Rodrigo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
The world has never been so eager for images as it is today! However, in the contemporary city, the seduction by the image has been increasingly anesthetized by the very atrophy of our perceptive capacity, after all, under the advent of speed and spectacularization we are steered to experiences where the routine, the glance, the passer-by look and the low definition of non-verbal languages form a set of behaviors that have shrunk our ability to look at the city. A type of glaucoma that facilitates the reading of some visual qualities of the landscape, but prevents it from being apprehended in its totality.